Children's sense of agency in preschool: a sociocultural investigation. Issue 2 (2nd April 2016) - Hilppö, Jaakko; Lipponen, Lasse; Kumpulainen, Kristiina; Rainio, Anna
ABSTRACT: This socioculturally informed study investigated children's sense of agency in relation to their everyday life in preschool. The empirical data comprised focus groups reflection situations wherein Finnish preschool children (n. 19, aged 6–7) reflected on their everyday life with the help of photographs and drawings they made. Building on a situative and discursive take on the sense of agency, the results of this study highlight the different forms of the sense of agency talked into being in the focus groups. The results also provide evidence of the different activities within which children's sense of agency was embedded. In addition, the study also engages with the notion of radical passivity to theoretically explore the borders of the concept of the sense of agency. In all, the study demonstrates the mundane side of children's sense of agency and its subtle dynamics in day-to-day life in preschool.